2023
DOI: 10.1186/s12909-023-04259-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of intellectual and developmental disability curriculum in international pre-graduate health professional education

Abstract: Background Despite the increasing global population of individuals with intellectual and developmental disabilities (IDD), this population remains especially vulnerable to health disparities through several factors such as a lack of access to sufficient medical care and poor determinants of health. To add, numerous studies have shown that healthcare professionals are still insufficiently prepared to support this population of patients. This review synthesizes the literature on current pre-gradu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Using NIH’s 12-point checklist for quality of pre-post studies without controls, we estimate having met ~ 6–8 of listed evaluation strengths, including: clear study question, pre-specified eligibility, sample representativeness, pre-specified outcomes and statistical analysis of pre-post change [ 31 ]. Further, partnering with PWIDDs in the design and implementation of our multi-modal curriculum aligns with recommendations from reviews of prior curricula [ 7 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using NIH’s 12-point checklist for quality of pre-post studies without controls, we estimate having met ~ 6–8 of listed evaluation strengths, including: clear study question, pre-specified eligibility, sample representativeness, pre-specified outcomes and statistical analysis of pre-post change [ 31 ]. Further, partnering with PWIDDs in the design and implementation of our multi-modal curriculum aligns with recommendations from reviews of prior curricula [ 7 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 50% of physicians lack confidence in caring for people with disabilities [ 5 ]. Medical school education on disability often reflect an ableist perspective [ 6 ]; when offered, it is rarely integrated across all years of medical school or fully embedded into the curriculum [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Co-production involves collaboration between clinical educators and healthcare recipients, in this case, people with intellectual disability, to design and deliver educational programs ( 39 ) and to ensure that their opinions and preferences are incorporated ( 40 ). Involving people with intellectual disability in the design and delivery of content for medical students and health professionals has been demonstrated to bring transformative change to the individuals involved, as well as to health professionals and health systems ( 41 ). A global systematic review looking at patient engagement across all health services only found a small number of studies that involved patients in the co-production of educational programs ( 42 ).…”
Section: The Need For Improved Clinician Educationmentioning
confidence: 99%
“…Co-production has also been associated with improved attitudes towards and awareness of the needs of people with intellectual disability ( 31 ), improved communication skills ( 33 ), and the sharing of power between patients and health professionals ( 42 ). Finally, learning about people’s lived experiences is enhanced when it is presented by the people themselves (co-education) within a sociocultural framework, as opposed to a purely medicalised perspective ( 41 ). This is crucial to facilitate learning about the importance of reasonable adjustments and adapting health assessments and management practices ( 33 ).…”
Section: The Need For Improved Clinician Educationmentioning
confidence: 99%
“…Literature on intellectual and developmental disability‐focused education for healthcare professionals is reviewed previously; however, previous reviews focused on education around disability in general (Rotenberg et al, 2022), addressing specific age groups such as paediatrics (Ceglio et al, 2019), and specific providers such as physicians (Adirim et al, 2021; Ceglio et al, 2019). A previous integrative review had discussion of the shift to interprofessional education and team competencies as contexts in which health professional education has developed (Vi et al, 2023). None addressed education of healthcare professionals in the contexts of overall workforce needs or the model of care or intersectionality or the participation of people with intellectual and developmental disabilities in the development and evaluation of programs.…”
Section: Introductionmentioning
confidence: 99%